Enhanced efficacy of Zingerone niosomes in attenuation of virulence and biofilm formation by Pseudomonas aeruginosa: An in-Vitro and ex-Vivo study (Funded Work) - Karuna Sharma; Sanjay Chhibber; Kusum Harjai (International Journal of Pharma and Bio Sciences, 2020)
Zingerone, a bioactive of Zingiber officinale, has enormous pharmacological properties and thus can be used as a promising candidate against various diseases. However, sparingly solubility in aqueous solution limits its potential as a therapeutic agent. To overcome this problem, Zingerone niosomes (Z-Niosomes) were prepared by thin-film hydration method using non-ionic surfactant and cholesterol. Synthesized Z-Niosomes were further characterised. The preparation showed a uniform size of 564.8 nm, PDI of 0.377 with -4.68 mV zeta potential and entrapment efficiency of 52%. The preparation was also found to be stable at different temperatures for 30 days. Z-Niosomes showed biofilm inhibition as well as eradication of the established biofilm, decreased the production of alginate. This was confirmed by field emission scanning electron microscope (FESEM). Various quorum sensing mediated phenotypes like protease, elastase, pyocyanin and hemolysin production were also attenuated on exposure to Z-Niosomes. Besides this, phagocytic uptake and intracellular killing of Z-Niosomes treated P. aeruginosa by murine macrophages were found to be more efficient and susceptibility to serum bactericidal killing was also enhanced. The results indicate that Z-Niosomes has the ability to attenuate the virulence of Pseudomonas aeruginosa resulting in increased vulnerability of the organism to innate immune responses. Z-Niosomes therefore can be used as anti-virulence agent against P. aeruginosa which can further potentiate the activity of zingerone.